Safety and Reliability – Safe Societies in a Changing World 2018
DOI: 10.1201/9781351174664-20
|View full text |Cite
|
Sign up to set email alerts
|

Safety climate and compliance in the Norwegian aquaculture industry—employees’ perceptions at different company levels

Abstract: The aquaculture industry is economically important in Norway, and the production is expected to increase in the future. Employees at the fish farms face a high risk of accidents compared to employees in other industries and the focus on safety from both industry and researchers has increased during the last decade. Adding to the knowledge on safety in aquaculture, the objective of this paper is to study employees' perception of safety climate, and whether aspects related to safety climate may predict employees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Previous studies have documented that operations using cranes and capstans involve risk of accidents [ 3 ]. Furthermore, organizational factors such as staffing, work hours, and maintenance are documented challenges for safety in aquaculture [ 8 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have documented that operations using cranes and capstans involve risk of accidents [ 3 ]. Furthermore, organizational factors such as staffing, work hours, and maintenance are documented challenges for safety in aquaculture [ 8 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the perceived practical relevance, these resources are not always in place. As documented in previous studies from the aquaculture industry, production in some operations may be prioritized over safety [ 19 , 38 , 41 ]. For example, the safety of personnel may be compromised when employees work up to 20 consecutive hours without sleep during large operations such as delousing of fish [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Organizational aspects influence the conditions of aquaculture employees [13].Organizational challenges such as prioritizing production at the expense of safety, long work hours and lack of rest during large operations, lack of training, inadequate maintenance and insufficient manning are some relevant examples that illustrate this [8,13,14,15,16,17,18]. Previous analyses also showed that 31% of 258 fish farmers agreed that it is uncomfortable to point out a lack of compliance with safety rules and procedures [13] and that near accidents are frequent among workers at the fish farms [17].…”
Section: Introductionmentioning
confidence: 99%